PENGARUH MODEL PEMBELAJARAN CORE BERBANTUAN GOOGLE SITES TERHADAP KETERAMPILAN MENULIS TEKS CERITA FANTASI - Andini Andini; Khaerunnisa Khaerunnisa (Universitas Sultan Ageng Tirtayasa, 2026)
ABSTRACT This study aims to determine the effect of the CORE (Connecting, Organizing, Reflecting, Extending) learning model assisted by Google Sites on the fantasy story writing skills of seventh-grade students. The background of this study is the low writing ability of students in developing ideas, plots, and text structures. The research method used is a quantitative approach with a posttest-only control group experimental design. The research sample consisted of an experimental class that received the CORE model assisted by Google Sites and a control class that used conventional learning. The instrument was a fantasy story writing test. The results showed that the posttest scores of the experimental class reached an average of 83.88, while the control class scored 65.27. The normality test showed that both groups were normally distributed with significance values of 0.019 and 0.014 (> 0.05), respectively. The homogeneity test also showed that the variances of the two groups were homogeneous (sig. 0.18 > 0.05). Furthermore, the t-test results showed a t-value of 10.653 with a significance level (2-tailed) of 0.000 < 0.05, so Ho was rejected and Ha was accepted. Thus, the CORE model assisted by Google Sites had a significant and effective influence on improving students' fantasy story writing skills.